Pembaharuan Hukum Islam Via Keterbukaan Landasan Filosofis: Ontologis, Epistemologis, Dan Aksiologis - Efendi, Athallah Keisa (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2024)
Updating Islamic law is essential to adapt to current social changes, given the limited coverage of the Prophet's holy books and hadith. This study seeks to investigate changes in Islamic law using the concepts of form, knowledge and values. The method used is a review by reading many books, magazine articles and science papers. These findings show that the philosophical foundation of sharia originates from principles revealed by God, but still maintains its adaptability to the ever-evolving societal and cultural environment. 'The epistemological view emphasizes important sources such as the Koran and Hadith as well as current strategies including maqasid sharia and maslahat.' Simultaneously, the ethical foundation emphasizes the incorporation of moral values, justice and societal welfare throughout the application of Sharia law, particularly in addressing contemporary issues such as gender equality, individual rights, and ecological conservation. This study finds that updating Sharia through a comprehensive philosophical perspective allows the fatwa to remain relevant and applicable to contemporary progress while maintaining religious-based principles. Conversations among clerics, religious leaders, and local gatherings play an important role in this thinking.